Absorption lines from magnetically driven winds in X-ray binaries – II. High resolution observational signatures expected from future X-ray observatories. Issue 1 (1st November 2022) - Chakravorty, Susmita; Petrucci, Pierre-Olivier; Datta, Sudeb Ranjan; Ferreira, Jonathan; Wilms, Joern; Jacquemin-Ide, Jonatan; Clavel, Maica; Marcel, Gregoire; Rodriguez, Jerome; Malzac, Julien; Belmont, Renaud; Corbel, Stephane; et al.
ABSTRACT: In our self-similar, analytical, magnetohydrodynamic (MHD) accretion–ejection solution, the density at the base of the outflow is explicitly dependent on the disc accretion rate – a unique property of this class of solutions. We had earlier found that the ejection index p 0.1 (M_acc r^p) is a key MHD parameter that decides if the flow can cause absorption lines in the high resolution X-ray spectra of black hole binaries. Here, we choose three dense warm solutions with p = 0.1, 0.3, 0.45 and carefully develop a methodology to generate spectra which are convolved with the Athena and XRISM response functions to predict what they will observe seeing through such MHD outflows. In this paper two other external parameters were varied – extent of the disc, r_o|_max = 10^5, 10^6 r_G, and the angle of the line of sight, i ∼ 10–25°. Resultant absorption lines (H and He-like Fe, Ca, Ar) change in strength and their profiles manifest varying degrees of asymmetry. We checked if (a) the lines and (ii) the line asymmetries are detected, in our suit of synthetic Athena and XRISM spectra. Our analysis shows that Athena should detect the lines and their asymmetries for a standard 100 ks observation of a 100 mCrab source – lines with equivalent width as low as a few eV should be detected if the 6–8 keV counts are larger than 10 4 –10 5 even for the least favourable simulated cases.